Treatment efficiency of Class I four-premolar and Class II malocclusion two maxillary premolar extraction protocols - Francisco, Rodolfo (2017)
This study aimed to compare the efficiency of 4-premolar extraction protocol in Class I malocclusion and 2-maxillary premolar extraction protocol in complete Class II malocclusions. Group 1 consisted of fifty patients retrospectively selected, initially presenting with Class I malocclusion, with an initial mean age of 13.66 years. Group 2 consisted of 36 patients initially presenting with full Class II malocclusion, with an initial mean age of 14.47 years. To assess the treatment efficiency index of each treatment protocol, the peer assessment rating (PAR) index was evaluated on the initial and final dental casts. Treatment efficiency index was calculated as the ratio between the percentage of PAR reduction and the treatment time. The occlusal outcomes at the post-treatment stage were evaluated by the PAR and OGS (Objective Grading System) indexes. T tests for independent samples were used for intergroup comparisons of the initial age, initial and final PAR, PAR reduction, PAR reduction percentage, treatment time, treatment efficiency, total OGS and OGS variables. Nonparametric Mann-Whitney U-tests were used for intergroup comparison of the FPAR occlusal variables and two OGS variables. There were no intergroup differences regarding PAR reduction, PAR reduction percentage, treatment time and treatment efficiency. Additionally, the occlusal outcomes at the post-treatment stage were similar in the groups. Therefore, it was concluded that the treatment efficiency and the occlusal outcomes were similar for both treatment protocols.